1999
DOI: 10.1111/j.1365-2621.1999.tb15122.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatments for Prevention of Persistent Pinking in Dark‐Cutting Beef Patties

Abstract: Food-grade oxidants and browning agents were compared for prevention of undesirable raw appearance of cooked dark-cutting (DC) beef patties. DC beef had higher pH (6.6 vs 5.7) and lower 24h oxidation-reduction potential (2190 vs 2108 mV) than controls, with higher cooked yield and cohesiveness, but lower beef flavor intensity scores. DC patties with lactic acid (LA) had acceptable cooked appearance and increased myoglobin (Mb) denaturation during cooking (77%-LA; 63%-normal control; 41%-DC control), but a tang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…These results agree with reports by Judge and Aberle (1980), Drerup and others (1981), Yasosky and others (1984), Chen and others (1993), and Moiseev and Cornforth (1999) who found improved oxidative stability in prerigor meat or in meat samples with elevated pH. Judge and Aberle (1980) concluded that, in ground salted porcine muscles, the partial inhibition of the lipid oxidation was due to high pH.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…These results agree with reports by Judge and Aberle (1980), Drerup and others (1981), Yasosky and others (1984), Chen and others (1993), and Moiseev and Cornforth (1999) who found improved oxidative stability in prerigor meat or in meat samples with elevated pH. Judge and Aberle (1980) concluded that, in ground salted porcine muscles, the partial inhibition of the lipid oxidation was due to high pH.…”
Section: Resultssupporting
confidence: 94%
“…This phenomenon may be related to the high pH of prerigor cooked beef. A similar observation was made for dark-cutting beef, pH 6.6, which gave reduced beef flavor intensity and increased off-flavor intensity when compared to beef with a typical pH, 5.7 (Moiseev and Cornforth 1999). This phenomenon may have contributed to panelist confusion especially when evaluating samples with inherently low levels of oxidation products.…”
Section: Resultssupporting
confidence: 60%
“…The method of Moiseeve and Cornforth (1999) was used in determining the change of ORP in meat. A pH/ion meter (Accumet 25, Fisher Scientific) connected to a platinum electrode filled with a 4 M-KCl solution saturated with AgCl was tightly inserted in the center of meat sample.…”
Section: Oxidation-reduction Potentialmentioning
confidence: 99%
“…Ground beef with higher pH values were related to higher a* values on the exterior of raw ground beef. Moiseev and Cornforth ( 1999) found higher myoglobin levels in high pH (6.6) ground beef compared to low pH (5.7) ground beef. However, no differences in a* values were observed between the two products when ground beef was spread thin and allowed to oxygenate before making patties.…”
Section: Resultsmentioning
confidence: 77%
“…It is generally assumed that longer cooking times or cooking patties to higher internal temperature will result in greater denaturation of muscle pigments; consequently providing more brown cooked color inside patties. Factors such as fat content (Troutt et al 1992;Liu and Berry 1996;Berry 1998ab;Berry and Bigner-George 2000), pH (van Laack et al 1997;Berry 1998a;Moiseev and Cornforth 1999), animal maturity (Hague et a!. 1994;Berry 1998a), myoglobin form (Warren et al 1996ab;Hunt et al 1999), added nonmeat ingredients (van Laack et al 1996a), product state (fresh, frozen, thawed) when cooked (van Laack et al 1996b;Berry 1998b;Hunt et al 1999;Bigner-George and Berry 2000;Lyon et al 2000) and time of purchase and location within the packaged product (Killinger et al 2000) have been shown to influence color of beef patties following cooking.…”
Section: Introductionmentioning
confidence: 99%